Effectiveness of Project-Based Entrepreneurship Learning Methods for High School Students - Hugo Aries Suprapto (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Entrepreneurship in Indonesia still needs to be encouraged again, so that the number of entrepreneurs increases. Project-based learning is an alternative method that requires practice which can have a big impact on students. Senior high schools (SMA) should be able to provide greater practical content in entrepreneurship subjects. The method used is the experimental method, pretest post test. The research results show that project-based methods can improve entrepreneurship learning outcomes in high school students.